Acquired von Willebrand Syndrome in a Child Following Berlin Heart EXCOR Pediatric Ventricular Assist Device Implantation: Case Report and Concise Literature Review. (October 2014) - Costello, John P.; Diab, Yaser A.; Philippe-Auguste, Michael; Jones, Melissa B.; Shankar, Venkat; Friedman, Kenneth D.; Nath, Dilip S.
The development of acquired von Willebrand syndrome (AVWS) after placement of a pulsatile-flow left ventricular assist device (LVAD) is rare and only recently recognized. We report the case of a young infant who was diagnosed with ventricular assist device (VAD)-related AVWS following implantation of a Berlin Heart EXCOR Pediatric Ventricular Assist Device (Berlin Heart Inc., The Woodlands, Texas, USA) for treatment of severe heart failure. Despite significant bleeding, the patient was successfully managed with von Willebrand factor-containing concentrate until VAD explantation led to definitive resolution of the AVWS. This case demonstrates that the possibility of this diagnosis should be considered in pediatric patients when extensive, nonsurgical bleeding is encountered after pulsatile-flow VAD implantation.